Vaccine potential of attenuated mutants of Corynebacterium pseudotuberculosis in sheep - Simmons, Cameron (2018)
Corynebacterium pseudotuberculosis, a gram-positive facultative intracellular bacterial pathogen, is the etiological agent of the economically important disease caseous lymphadenitis (CLA) in both sheep and goats. Attenuated mutants of C. pseudotuberculosis have the potential to act as novel vaccines against CLA and as veterinary vaccine vectors. In this report, we have assessed the virulence of both aroQ and pld mutants of C. pseudotuberculosis in sheep and concurrently their capacity to act as vaccines against homologous challenge. The results suggest that aroQ mutants of C. pseudotuberculosis are attenuated with regard to both lymph node persistence and vaccination site reactogenicity. Immunologically, aroQ mutants failed to elicit detectable specific gamma interferon (IFN-gamma)-secreting lymphocytes and induced low levels of antibodies to C. pseudotuberculosis culture supernatant antigens. Following subcutaneous vaccination, the immune responses induced by aroQ mutants did not protect sheep from infection with the wild-type strain but did appear to reduce the clinical severity of disease resulting from challenge. Conversely, an attenuated C. pseudotuberculosis strain expressing an enzymatically inactive phospholipase D exotoxin, when used as a vaccine, elicited a protective immune response. Protection appeared to correlate with in vivo persistence of the vaccine strain, the induction of IFN-gamma-secreting lymphocytes, and relatively high levels of antibodies to culture supernatant antigens. The results suggest that aroQ mutants of C. pseudotuberculosis may be overly attenuated for use as a CLA vaccines or as vaccine vectors.